Interaction between Nuclear Receptor and Alpha-Adrenergic Agonist Subtypes in Metabolism and Systemic Hemodynamics of Spontaneously Hypertensive Rats - Sheryar Afzal; Munavvar Abdul Sattar; Ibrahim Albokhadaim; Ali Attiq; Mahmoud Kandeel; Aimi Syamima Abdul Manap; Sameer M. Alhojaily (PPAR Research)
Partial and full PPAR-γ agonists have shown promising effects and antihypertensive and antidiabetic agents through increased plasma adiponectin concentration. This study is aimed at examining the role of PPAR-γ, alpha-adrenoceptors, and adiponectin receptors in the modulation of vasopressor responses to angiotensin II (Ang II) and adrenergic agonists, after a subset treatment of partial and full PPAR-γ agonists, each individually, and also when coupled with adiponectin in SHRs. The antioxidant potential and metabolic indices for these animals were also determined. Group I (WKY) and group II (SHR) were designated as normotensive control and hypertensive control, respectively. Groups III (SHR) and IV (SHR) received irbesartan (30 mg/kg) and pioglitazone (10 mg/kg) orally for 28 days, and groups V (SHR), VI (SHR), and VII (SHR) were treated with adiponectin (2.5 μg/kg) intraperitoneally alone, in combination with irbesartan, and in combination with pioglitazone, respectively, from days 21 to 28 only. On day 29, sodium pentobarbitone (60 mg/kg) was used to anesthetize all test animals, and systemic hemodynamic and plasma adiponectin concentrations and in vitro and in vivo antioxidant potential were measured. As compared to the WKY control, the SHR control group’s noninvasive blood pressure and basal mean arterial pressure were significantly greater, along with increased arterial stiffness, lower plasma nitric oxide, adiponectin concentration, and antioxidant enzyme levels (all P<0.05). However, they were gradually normalized by single drug treatments in all groups, and to a greater extent in the SHR + Irb + Adp group (P<0.05). In the acute study, the dose dependant mean arterial pressure responses to intravenously administered adrenergic agonists and angiotensin-II were significantly larger in SHRs as compared to WKY by 20-25%. Adiponectin alone and in combination significantly blunted vasopressor responses to these alpha-adrenergic agonists in the SHR + Pio + Adp group by 63%, whereas attenuated responses to ANG-II administration to 70% in SHR + Irb + Adp. In conclusion, the combined treatment of adiponectin with PPAR-agonists reduced the systemic vascular responses to adrenergic agonists and improved arterial stiffness. This an evidence of the interaction of adiponectin receptors, PPAR-γ, alpha-adrenoceptors, and ANG-II in the systemic vasculature of SHRs. A significant level of synergism has also been proved among full PPAR-γ agonists and adiponectin receptors.